2012
DOI: 10.1016/j.fob.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis F‐box protein containing a Nictaba‐related lectin domain interacts with N‐acetyllactosamine structures

Abstract: Highlights► Recombinant expression of a new type of Arabidopsis F-box protein. ► Arabidopsis F-box-Nictaba protein is a functional lectin. ► Arabidopsis F-box-Nictaba recognizes N-acetyllactosamine and Lewis structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 39 publications
0
22
1
Order By: Relevance
“…2012; Stefanowicz et al, 2012). Further studies are necessary to elucidate the carbohydrate-binding specificities of NLL proteins in other species.…”
Section: Discussionmentioning
confidence: 99%
“…2012; Stefanowicz et al, 2012). Further studies are necessary to elucidate the carbohydrate-binding specificities of NLL proteins in other species.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, these possibilities are not mutually exclusive and perhaps occur in parallel. Interestingly, some F-box proteins containing a lectinlike domain can bind to various carbohydrate epitopes including core a1,3-fucose, implying a role for complex N-glycans in protein turnover (Stefanowicz et al, 2012). In addition, a recent report showed that KOR1 is part of the cellulose synthase complex required for normal motility and intracellular trafficking of the CSC (Vain et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Glycan array analyses revealed the F-box protein encoded by At2g02360 exhibits carbohydrate binding activity toward N - and O -glycans with N -acetyllactosamine (LacNAc; Galβ1–3GlcNAc and Galβ1–4GlcNAc) and poly-LacNAc structures as well as with Lewis A (Galβ1–3(Fucα1–4)GlcNAc), Lewis X (Galβ1–4(Fuca1–3)GlcNAc), Lewis Y (Fucα1–2Galβ1–4(Fucα1–3)GlcNAc), and type-1 B motifs (Galα1–3(Fucα1–2)Galβ1–3GlcNAc. Since these glycan structures have been reported in bacteria, viruses, and animals rather than in plants the physiological importance of this glycan interaction remains enigmatic (Lannoo et al, 2008; Stefanowicz et al, 2012). Furthermore, the same Arabidopsis F-box Nictaba protein was shown to interact with core members of an E3-type ubiquitin ligase complex which resulted in the hypothesis assuming a role of the Nictaba domain in glycoprotein degradation (Takahashi et al, 2004; Arabidopsis Interactome Mapping Consortium, 2011).…”
Section: Pathogen Recognition Based On Protein–carbohydrate Interactionsmentioning
confidence: 99%